Creating the Market University : How Academic Science Became an Economic Engine - Berman, Elizabeth Popp, 1975- (Book collections on Project MUSE., 2012)
American universities today serve as economic engines, performing the scientific research that will create new industries, drive economic growth, and keep the United States globally competitive. But only a few decades ago, these same universities self-consciously held themselves apart from the world of commerce. Creating the Market University is the first book to systematically examine why academic science made such a dramatic move toward the market. Drawing on extensive historical research, Elizabeth Popp Berman shows how the government--influenced by the argument that innovation drives the e.